Longitudinal Peripartum Assessment of Retinal Nerve Fiber Layer Thickness and Optic Nerve Sheath Diameter in Women with Preeclampsia and Normotensive Pregnant Controls - Raffaella L. Fantin; Franziska Huter; Alexander Franchi; Daniel Egger; Reinhard Angermann; Lisa Schlosser; Samira Abdel Azim; Katharina Knoll (Journal of Clinical Medicine, 2026)
Background/Objectives: Preeclampsia is associated with endothelial dysfunction and neurological morbidity. Non-invasive ocular imaging may offer insight into subclinical ocular changes associated with neurological involvement. This prospective single-center pilot study evaluated retinal nerve fiber layer (RNFL) thickness, optic nerve sheath diameter (ONSD), and angiogenic biomarkers in women with and without preeclampsia across the peripartum period. Methods: Pregnant women with preeclampsia and normotensive controls were enrolled at a tertiary center. RNFL thickness was assessed by optical coherence tomography and ONSD by transbulbar ultrasound at three predefined visits: antepartum, early postpartum, and late postpartum. The soluble fms-like tyrosine kinase-1/placental growth factor (sFlt-1/PlGF) ratio was determined at the antepartum visit. Group comparisons, longitudinal changes, and exploratory correlations were analyzed, with paired-eye dependence addressed using generalized estimating equations (GEE). Results: Thirty-eight women were included; after reclassification of three controls who developed preeclampsia, 15 women were analyzed in the preeclampsia group and 23 in the control group. RNFL thickness was numerically higher in women with preeclampsia across visits; GEE analyses accounting for paired-eye measurements showed exploratory between-group differences at the early postpartum visit. ONSD did not differ significantly between groups, and no participant had a bilateral mean ONSD > 5.8 mm. No significant between-group differences in longitudinal change from early to late postpartum were observed. Exploratory analyses did not demonstrate a consistent association between the sFlt-1/PlGF ratio and the imaging parameters. Conclusions: RNFL thickness was numerically higher in women with preeclampsia, whereas ONSD showed no clear separation between groups. The findings remain exploratory and do not establish a diagnostic or prognostic role for either imaging parameter. Larger prospective studies are needed to determine the clinical relevance of non-invasive ocular imaging in preeclampsia.